Identification of a New Compound as α-Glucosidase Inhibitor from Aspergillus aculeatus - Rizna Triana Dewi; Asep Suparman; Hanny Mulyani; Akhmad Darmawan; Puspa Dewi Narrij Lotulung (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2016)
Terestrial fungi are of great importance as potential sources of pharmaceutical agent. Aspergillus aculeatus, a fungus isolated from soil sample collected in Indonesia, was cultured in liquid media to investigate a novel compound as inhibitor α-glucosidase. The mycelium extract of A. aculeatus shows potential activity against Saccharomyces cereviseae α-glucosidase and mild activity against mammalian α-glucosidase with IC50 values of 9.57 µg/mL and 470.76 mg/mL, respectively. Enzyme assay-guided fractionation of this extract afforded rubrofusarin (1). Rubrofusarin, a linear naphtho-γ-pyrone, is a natural pigment from Aspergillus sp. Interestingly, compound 1 shows potential inhibitory activity against mammalian α-glucosidase (IC50 of 92.7 µg/mL), but no to S. cereviseae α-glucosidase. The results suggest that A. aculeatus is a promising natural source as a lead compound in the discovery of antidiabetic drug.